HIV and pregnancy in adolescents and young adults: epidemiological profile and factors associated with infection (Research, Society and Development, 2020)
This study aimed to evaluate the prevalence of Human Immunodeficiency Virus (HIV) infection and risk factors associated with transmission in pregnant women of a public maternity hospital in Piauí. The cutoff point was October 2015 and June 2016, where data were collected from 412 pregnant women up to 26 years of age, related to sociodemographic characteristics, factors associated with infection, and obstetric and gynecological factors. Correlations were verified by Chi-square test (χ2), establishing a significance level below 5% (p